PKCα: Prospects in Regulating Insulin Resistance and AD - Mishra, Devanshi; Dey, Chinmoy Sankar (Trends in endocrinology and metabolism, 2021)
Protein kinase C alpha (PKCα) is known to participate in various signaling pathways due to its ubiquitous and dynamic characteristics. Previous studies report that PKCα abrogates peripheral insulin resistance, and recent publications show that it takes part in regulating Alzheimer’s disease (AD). Based on evidence in the literature, we have highlighted how many of the substrates of PKCα in its signal transduction cascades are common in AD and diabetes and may have the capability to regulate both diseases simultaneously. Signaling pathways crosslinking these two diseases by PKCα have not been explored. Understanding the complexities of PKCα interactions with common molecules will deepen our understanding of its regulation of relevant pathophysiologies and, in the future, may broaden the possibility of using PKCα as a therapeutic target. Previous studies have indicated that protein kinase C alpha (PKCα) expression and activity is reduced in cancers, whereas its activity is enhanced in Alzheimer’s disease (AD). Thus, an anticancer drug, which is supposed to increase PKCα levels in cancer, might create severe complications if the patient happens to be an AD patient or a prospective AD patient.Opposite expression profiles of PKCα occur in patients with insulin-resistant diabetes compared with insulin-sensitive subjects, opening up questions about the involvement of PKCα in diabetes.Neuronal insulin resistance is known to be associated with AD, and neuronal PKCα regulates many substrates, which seems to overlap between insulin-resistant diabetes and AD. Understanding this crosslinking of signaling molecules in both insulin-resistant diabetes and AD might lead to a better understanding of how PKCα regulates two dissimilar pathophysiologies.